Antimicrobial, antioxidant and anticancer activities of mangrove associated bacterium Bacillus subtilis subsp. subtilis RG. Issue 2 (April 2015) - Ramasubburayan, R.; Sumathi, S.; Magi Bercy, D.; Immanuel, G.; Palavesam, A.
Abstract In the present investigation an attempt was made to explore the antimicrobial, antioxidant and anticancer activities of ethyl acetate extract of mangrove associated bacterium Bacillus subtilis subsp. subtilis RG. Antimicrobial activity results revealed that, the extract had strongly inhibited growth of gram positive than gram negative bacterial strains and also significantly (P<0.05) inhibited the growth of fungal strains. Minimum inhibitory concentration (MIC) of extract by microbroth dilution test against bacterial and fungal strains was in the range from 50 to 210 and 150 to 250 µg ml−1; whilst minimum bactericidal/fungicidal concentration (MBC/MFC) was ranged from 90 to 250 and 200 to 300 µg ml−1, respectively. Antioxidant assay revealed that, this extract had maximum DPPH radical scavenging effect (75.79±5.41%) and reducing power (0.752±0.021 OD) at 1000 µg ml−1. MTT assay showed potent cytotoxic activity against human breast adenocarcinmoa cells (MCF-7) with the IC50 value of 46.64±0.79 µg ml−1. This study tends to indicate that, B. subtilis subsp. subtilis RG isolated from mangrove ecosystem could be potentially explored for the development of new therapeutic agents.